Type IV Esophageal Atresia with Nasogastric Tube in Stomach - Jose María Lloreda-García; Sandra Sevilla-Denia; Jose Luis Leante-Castellanos; Carmen Fuentes-Gutiérrez (EL-Med-Pub, 2017)
Please see fulltext.